Factors influencing pregnancy outcome in women with vaginal bleeding before midpregnancy: a prospective case control study - Guruvare, Shyamala; Medipalli, Priyanka; Urala, Srinivasa M.; Rai, Lavanya; Hebbar, Shripad; Adiga, Prashanth (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pregnancy complications are observed to be higher among women with first trimester bleeding compared to those without bleeding. We intended to compare the obstetric outcome based on details of bleeding episodes, i) in groups with spotting, bleeding and brown discharge; ii) in those with or without subchorionic haemorrhage; and iii) between single versus recurrent episodes of bleeding. Methods: We conducted a prospective case control study involving the women enrolled for antenatal care before 20 weeks of gestation. Information was collected regarding the details of bleeding, the pregnancy complications and the perinatal outcome. The outcome variables were analysed as per the study objectives using SPSS version 16.0. Results: Pregnancies complicated by bleeding before 20 weeks of gestation were associated with the significant increase in preterm premature rupture of the membranes [P 0.045; RR 4.8 (95% CI 1.5-15)], intrauterine growth restriction [P 0.039; RR 2.5(95% CI 1.1-6.3)], oligohydramnios [RR 4.3 (95% CI 2-9)], hypertension [RR 1.8 (95% CI 1.07-3.09)], small for gestational age babies [P 0.047; RR 2.7 (95% CI 1.2-6.1)] and NICU admissions [P 0.016; RR 2.7 (95% CI 1.1-6.5)]. Fresh bleeding/ spotting were associated with increased pregnancy complications (P 0.048) compared to brownish discharge. Presence of subchorionic hemorrhage on ultrasound in women with vaginal bleeding was associated with increased pregnancy complications (P 0.044). No difference in terms of complications, mean gestational age and mean birth weight was noted depending on the number of episodes of bleeding. Conclusions: Fresh bleeding and presence of subchorionic hemorrhage predict a poor pregnancy outcome in women with bleeding before 20 weeks of pregnancy.